Stem Cells and Cardiac Regeneration - Madonna, Rosalinda (Stem Cell Biology and Regenerative Medicine, 2016)
This book provides an update of recent advances in the basic and clinical applications of cell-based therapies for myocardial repair and regeneration in ischemic heart disease (IHD) and heart failure (HF). The first sections of the book illuminate basic aspects of stem cells such as definitions, isolation criteria and characterization of embryonic and adult stem cells, as well as pluripotent stem cells and tissue specific progenitor and stem cells. In the following section, the text examines the role of critical regulators of stem cell differentiation in myocardial regeneration, that include circadian rhythyms, microRNAs, epigenetics, microvescicles, and exosomes. The text concludes with a review of the use of stem/progenitor cells in cardiac regeneration and discuss current controversies, unresolved issues, challenges, and future directions. Stem Cells and Cardiac Regeneration is addressed to a wide audience consisting of cardiologists, clinicians, and research scientists, who will learn new concepts in cardiovascular regeneration and repair with special focus on molecular mechanisms and therapeutic potential for cardiovascular regeneration. .